2022
DOI: 10.1016/j.jare.2021.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of different Bacteroides vulgatus strains against lipopolysaccharide-induced acute intestinal injury, and their underlying functional genes

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
56
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 87 publications
5
56
1
Order By: Relevance
“…Some strains of Bacteroides are believed to be probiotics, and they participate in regulating the dynamic balance of GM and in increasing host immunity. 50 , 51 In the current study, TPS decoction increased the abundance of Bacteroides in T2DM mice. TPS decoction may promote the recovery of GM dynamic balance by increasing the content of Bacteroides , thereby improving T2DM symptoms.…”
Section: Discussionsupporting
confidence: 55%
“…Some strains of Bacteroides are believed to be probiotics, and they participate in regulating the dynamic balance of GM and in increasing host immunity. 50 , 51 In the current study, TPS decoction increased the abundance of Bacteroides in T2DM mice. TPS decoction may promote the recovery of GM dynamic balance by increasing the content of Bacteroides , thereby improving T2DM symptoms.…”
Section: Discussionsupporting
confidence: 55%
“…In addition, it has been confirmed that a variety of members in Bacteroidetes and Firmicutes provide a beneficial role in host digestion in broilers [ 35 ]. The genus Bacteroides and Phascolarctobacterium display a positive effect on host health and disease resistance [ 36 ]. The decreased abundance of Bacteroides and Phascolarctobacterium was observed in patients with inflammatory bowel disease [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The genus Bacteroides and Phascolarctobacterium display a positive effect on host health and disease resistance [ 36 ]. The decreased abundance of Bacteroides and Phascolarctobacterium was observed in patients with inflammatory bowel disease [ 36 , 37 ]. Our study also found that MMT increased the relative abundance of Bacteroides and Phascolarctobacterium, and decreased the relative abundance of Olsenella, Ruminococcaceae-UCG -009 .…”
Section: Discussionmentioning
confidence: 99%
“…The genus Bacteroides exhibits a positive effect on host health and disease resistance, and has attracted widespread attention (43). The reduced abundance of Bacteroides was observed in patients with inflammatory bowel diseases (44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%